Assessing fitness to drive after stroke: A survey investigating current practice among occupational therapists in Ireland. Issue 2 (12th October 2018) - Stack, Aisling Helen; Duggan, Orla; Stapleton, Tadhg
Abstract : Purpose: The assessment of fitness to drive after stroke is an emerging area of occupational therapy practice in Ireland. Despite this, little is known about occupational therapists' evaluation practices, and there are no internationally agreed clinical guidelines to inform best practice. The purpose of this paper is to investigate occupational therapy evaluation practices for fitness to drive after stroke in Ireland. Design/methodology/approach: This is a cross-sectional study design targeting occupational therapists working with people after stroke using an online survey. Summary and descriptive statistics were used to analyse the returned surveys. Findings: In total, 47 occupational therapists participated. Off-road driving assessment was completed by 68 per cent of respondents. Functional assessment and non-driving-specific assessments were most widely used and perceived to be the most useful in informing the off-road assessment. A total of 89 per cent referred clients for on-road assessments; however, some referred without first completing an off-road assessment. The therapists who completed formal post graduate education/training in driving assessment reported greater confidence and competence in their skills and ability to assess fitness to drive. A vast majority of participants agreed that clinical guidelines regarding best practice in this area would be beneficial. Research limitations/implications: A majority of occupational therapists are assessing fitness to drive after stroke in Ireland with non-driving-specific assessments and functional observations; however, there are many gaps and wide variations between services. Education/training in evaluating fitness to drive after stroke is recommended. The development of clinical guidelines to inform practice would facilitate a consistent approach nationally. Originality/value: This is the first study completed in Ireland to investigate occupational therapy evaluation practices for fitness to drive after stroke.